2019
DOI: 10.1080/10408398.2019.1703642
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin C and E on exercise-induced physiological adaptations: a systematic review and Meta-analysis of randomized controlled trials

Abstract: A Bowden (2019) The effects of vitamin C and E on exercise-induced physiological adaptations: a systematic review and Meta-analysis of randomized controlled trials. Critical Reviews in Food Science and Nutrition, 60 (21). pp. 3669-3679.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…In another study on the effects of vitamin E and C supplementation on endurance performance, Merry and Ristow (2016) [ 7 ] noted similar findings reporting no effect of supplementation on VO 2 max. A recent systematic review concluded that vitamin C and/or vitamin E has no negative effect on VO 2 max [ 49 ].…”
Section: Vitamin E As An Antioxidant Supplementmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study on the effects of vitamin E and C supplementation on endurance performance, Merry and Ristow (2016) [ 7 ] noted similar findings reporting no effect of supplementation on VO 2 max. A recent systematic review concluded that vitamin C and/or vitamin E has no negative effect on VO 2 max [ 49 ].…”
Section: Vitamin E As An Antioxidant Supplementmentioning
confidence: 99%
“…Regarding the effects of vitamin E alone or combined with vitamin C supplementation (in conjunction with strength training) on strength gains, five studies [ 50 , 52 , 55 , 60 , 61 ] have been done and reported neither positive nor negative effects on strength gain. A recent comprehensive meta-analysis [ 49 ] provided evidence that vitamin E supplementation alone or combined with vitamin C neither enhances nor blunts exercise-induced training adaptations, including changes in aerobic capacity, muscle strength, or lean mass and endurance performance. However, it is unclear whether in the state of deficiency or inadequate intake, these supplements would be beneficial for this purpose.…”
Section: Vitamin E As An Antioxidant Supplementmentioning
confidence: 99%
“…Relevant information was extracted and tabulated into a Microsoft Excel Spreadsheet by the first author and validated by the second author. The data extraction sheet was adapted form an example provided by the Introduction to Systematic Reviews Course at York University, UK, and has previously been used to extract similar data (Clifford, Jeffries, Stevenson, & Davies, 2019). Collected data included: (1) authors and year of publication;…”
Section: Data Extractionmentioning
confidence: 99%
“…However, this is not necessarily the case in body fluids, such as blood plasma, where enzymes are not normally present and, therefore, non-enzymatic molecules have a crucial role in RONS regulation [54,55]. Below, we limit our discussion to three non-enzymatic antioxidant molecules (ascorbate, α-tocopherol, and glutathione) that the research so far has shown to play important role in redox regulation and for which there is sufficient quantitative data [56,57].…”
Section: Antioxidantsmentioning
confidence: 99%